2018
DOI: 10.1002/sctm.17-0258
|View full text |Cite
|
Sign up to set email alerts
|

Compressed Collagen Enhances Stem Cell Therapy for Corneal Scarring

Abstract: Stem cells from human corneal stroma (CSSC) suppress corneal stromal scarring in a mouse wound‐healing model and promote regeneration of native transparent tissue (PMID:25504883). This study investigated efficacy of compressed collagen gel (CCG) as a vehicle to deliver CSSC for corneal therapy. CSSC isolated from limbal stroma of human donor corneas were embedded in soluble rat‐tendon collagen, gelled at 37°C, and partially dehydrated to a thickness of 100 µm by passive absorption. The CCG disks were dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…Corneal cell type, isolation from donor corneas Scaffold not detected in rabbits 35 , no evidence in rabbits 43 , scar suppression in mice 76 No evidence available 57,58…”
Section: Human Donor Corneal Cellsmentioning
confidence: 99%
“…Corneal cell type, isolation from donor corneas Scaffold not detected in rabbits 35 , no evidence in rabbits 43 , scar suppression in mice 76 No evidence available 57,58…”
Section: Human Donor Corneal Cellsmentioning
confidence: 99%
“…Our previous work has shown that human corneal stroma contains a population of cells (human corneal stem cells, CSSC), which exhibit properties of MSCs and differentiate to corneal keratocytes [2][3][4][5][6][7][8][9]. These cells also block deposition of opaque scar tissue in a corneal wound healing model and elicit regeneration of normal, transparent stromal extracellular matrix [7,8,[10][11][12]. An important aspect of tissue regeneration effected by MSCs depends on their modification of tissue immune response by secretion of soluble factors to their environment [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Compressed collagen hydrogels which contained hCSSCs was reported to suppress scar formation and improve regeneration of the injured tissue in mouse models with corneal scars in the anterior stroma. Lower inflammatory immune response was detected when fibrin gel was applied instead of sutures to implant the hydrogel to the damaged stroma [133].…”
Section: 222mentioning
confidence: 99%